2016
DOI: 10.4049/jimmunol.1501789
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Aryl Hydrocarbon Receptor by 10-Cl-BBQ Prevents Insulitis and Effector T Cell Development Independently of Foxp3+ Regulatory T Cells in Nonobese Diabetic Mice

Abstract: AhR activation by high affinity ligands mediates immunosuppression in association with increased regulatory T cells, making this transcription factor an attractive therapeutic target for autoimmune diseases. We recently discovered 10-chloro-7H-benzimidazo[2,1-a]benzo[de]iso-quinolin-7-one (10-Cl-BBQ), a nanomolar affinity AhR ligand with immunosuppressive activity and favorable pharmacologic properties. Here, we tested the consequences of AhR activation in the NOD model. Oral 10-Cl-BBQ treatment prevented isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 44 publications
3
48
1
Order By: Relevance
“…1). Moreover, there is increasing evidence that the AhR plays a prominent role in physiology and pathophysiology including important roles in the immune function, autoimmunity, gastrointestinal function, inflammation and cancer (Benson and Shepherd 2011; Boitano et al 2010; Ehrlich et al 2016; Esser 2012; Kerkvliet et al 2009; Marshall and Kerkvliet 2010; Murray et al 2010; Punj et al 2014; Quintana et al 2008; Veldhoen et al 2008) and development of selective AhR modulators is a promising new area of pharmacological research, particularly for cancer chemotherapy (Murray et al 2014; Safe et al 2013). …”
Section: The Ahr and Its Physiological Rolementioning
confidence: 99%
“…1). Moreover, there is increasing evidence that the AhR plays a prominent role in physiology and pathophysiology including important roles in the immune function, autoimmunity, gastrointestinal function, inflammation and cancer (Benson and Shepherd 2011; Boitano et al 2010; Ehrlich et al 2016; Esser 2012; Kerkvliet et al 2009; Marshall and Kerkvliet 2010; Murray et al 2010; Punj et al 2014; Quintana et al 2008; Veldhoen et al 2008) and development of selective AhR modulators is a promising new area of pharmacological research, particularly for cancer chemotherapy (Murray et al 2014; Safe et al 2013). …”
Section: The Ahr and Its Physiological Rolementioning
confidence: 99%
“…CD4 + T cells are particularly sensitive targets for AhR regulation, and activation of AhR by exogenous ligands results in suppression of Th1‐, Th2‐ and Th17‐dependent immunity . Accordingly, treatment of mice with AhR ligands has been shown to ameliorate the development of several T‐cell dependent autoimmune diseases, such as type 1 diabetes , inflammatory bowel disease , and experimental autoimmune encephalomyelitis , as well as to suppress transplant rejection and inhibit graft‐versus‐host (GVH) disease . The potent efficacy of AhR ligands in these preclinical models supports the development of AhR ligands for therapeutic use in prevention and treatment of immune‐mediated diseases .…”
Section: Introductionmentioning
confidence: 95%
“…With the use of TCDD ( 3 ) it has been reported that upregulation of AhR resulted in downregulation of immune responses . More recent work demonstrates that activation of the AhR pathway results in the increased frequency of regulatory T cells (Tregs) that lead to immune tolerance . Preliminary reports suggest that TNBC and ER‐negative patients with higher densities of Tregs experienced significantly longer overall and disease‐free survival, than those with lower Treg levels …”
Section: Ahr and Immunitymentioning
confidence: 99%
“…10‐Cl‐BBQ showed high AhR affinity and promoted cytosol to nuclear translocation of the AhR at nanomolar concentrations. Importantly 33 with a short serum half‐life (2 hours) and no acute toxicity at therapeutic doses, was found to induce Tregs in vivo, leading to the possibility of the AhR to be targeted for immune‐mediated diseases …”
Section: Exogenous Ligandsmentioning
confidence: 99%